Isolation and Identification of Petroleum oil Degrading Bacterial Strain from the Contaminated Soil of Alwar Region, Rajasthan, India. - MOHAN LAL KURI; SHIKHA ROY (International Journal of Pharma and Bio Sciences, 2018)
Growth of nation with economic advancement released few hazardous wastes into environment; and reduces the function potential of ecological systems. Among the natural resources regarding energy aspect, petroleum contributed much more than others. The waste byproducts are creating health hazards to human via contamination of soil and water. A study was conducted and isolated the oil degradation bacterial to reduce the hazardous waste concentration from contaminated sites. Many bacteria were isolated from different selected sites by using serial dilution method. In this experiment, petroleum byproducts are used as a source of food for microorganisms. Therefore for their isolation selective media containing 2T oil as sole source of carbon and energy was used. The bacterial colonies which developed on the Bushnell-Hash Agar (BHA) medium containing hydrocarbon as a source of energy were selected for further studies for their cultural characteristics and colony morphology. By putting the plates across the eye level, their morphology was observed with naked eyes. The general form of the colony and shape of the edge or margin was determined from looking down at the top of the colony. The nature of the colony elevation is apparent when viewed from the side as the plates. Colony characteristics (shape, margin, elevation, color etc.) of the bacterial isolates were observed. After it biochemical test was done to identify up to genus level. The biodegradation of 2T engine oil was carried out by gravimetric analysis. Such type of study can be useful for the remediation of oil contaminated soil across the globe.